The Effectiveness of Resistance Band Training on Lower Extremity Muscle Strength in Elderly Women to Prevent Fall Risk - Rayhan Geofahmi,; Risal Permana,; Aditya Tegar Permana,; M. Arief Setiawan,; A. Ine Aprilia Damai,; Aprillia Wulan Utari, (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
The increasing elderly population has led to a rise in health-related problems, particularly the decline in physical function caused by aging processes such as sarcopenia, which contributes to a higher risk of falls. Elderly women are more vulnerable to reduced muscle strength; therefore, effective and safe interventions are needed. This study aimed to analyze the effectiveness of resistance band training on lower extremity muscle strength and its implications for reducing fall risk in elderly women. The study employed a quantitative approach with a quasi-experimental pretest–posttest control group design. The sample consisted of 20 elderly women (aged 60–74 years), divided into an experimental group (n=10) and a control group (n=10). The intervention consisted of resistance band training conducted for 6 weeks, with a frequency of three sessions per week. The instruments used were the 30-Second Chair Stand Test to measure muscle strength and the Timed Up and Go Test (TUG) to assess fall risk. Data were analyzed using paired sample t-tests and independent sample t-tests with a significance level of 0.05. The results showed a significant increase in muscle strength in the experimental group (p<0.05) compared to the control group. In addition, there was a significant reduction in TUG time in the experimental group, indicating a lower risk of falls. The findings suggest that resistance band training is effective in improving neuromuscular adaptation, muscle strength, and functional ability in the elderly. In conclusion, resistance band training has proven effective in increasing lower extremity muscle strength and reducing fall risk in elderly women. Therefore, it can be recommended as a safe, practical, and applicable exercise intervention.